Kajian Hukum Progresif Terhadap Pasal 2 UU No 1 Tahun 1974 Tentang Perkawinan - Martha Eri Safira (Justicia Islamica, 2012)
A marriage, refers to legal law of marriage article 2, is legitimate if the doers marry under their religious law. A legal marriage refers both to doers’ religious procedures and to society perspective. Nevertheless, the most important thing is that government trough its officers should legalize the marriage for legal reason. An illegal marriage and divorce will drive to problematic level. It is probably legal for society but illegal to marriage officers as ”˜pencatat nikah’ who base their legality to legal law of marriage. The former, consequently, takes ”˜negative domino effect’ not only for a wife but also for her kids legally and socially. This short paper is to elaborate legal law of marriage by using both progressive law, shari>’ah law and law educational system. Do progressive law and the others afford and give solution to protect women and their kids legally and socially?